(untitled) (Orfeu, 2016)
Regional songs are a primary mode of symbolic production (or reproduction) for identity discourses in Tocantins, Brazilian state created in 1989. Review of studies on Tocantins cultural identity, interviews with skilled listeners and analysis of phonograms substantiate a discussion of the exchange process and meanings associated with the inclusion of this repertoire in the cultural dynamics of identity symbolic negotiation. The resulting tensions and contradictions can be summarized in two poles: on the one hand, the political territory, aligned to legitimacy of autonomy and power; on the other hand, the policy of the territory in which the idea of identity emerges as an expression of shared cultural experiences.